2022
DOI: 10.3389/fphar.2022.921394
|View full text |Cite
|
Sign up to set email alerts
|

EGCG protects the mouse brain against cerebral ischemia/reperfusion injury by suppressing autophagy via the AKT/AMPK/mTOR phosphorylation pathway

Abstract: Stroke remains one of the leading reasons of mortality and physical disability worldwide. The treatment of cerebral ischemic stroke faces challenges, partly due to a lack of effective treatments. In this study, we demonstrated that autophagy was stimulated by transient middle cerebral artery occlusion/reperfusion (MCAO/R) and oxygen-glucose deprivation/reoxygenation (OGD/R). Treatment with (−)-epigallocatechin-3-gallate (EGCG), a bioactive ingredient in green tea, was able to mitigate cerebral ischemia/reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(84 reference statements)
1
2
0
Order By: Relevance
“…EGCG itself could produce hypoxic protection and promote cell differentiation by regulating Akt signaling. 37,38 In this study, EPLA promoted the phosphorylation of S473 of Akt and T28 of FoxO4. Combined with the results of previous studies, we speculated that EPLA could inhibit the nuclear entry of Foxo4 transcription factor by promoting the phosphorylation of Akt S473, thereby inhibiting the production of atrophin (Figure 6).…”
Section: Discussionsupporting
confidence: 52%
“…EGCG itself could produce hypoxic protection and promote cell differentiation by regulating Akt signaling. 37,38 In this study, EPLA promoted the phosphorylation of S473 of Akt and T28 of FoxO4. Combined with the results of previous studies, we speculated that EPLA could inhibit the nuclear entry of Foxo4 transcription factor by promoting the phosphorylation of Akt S473, thereby inhibiting the production of atrophin (Figure 6).…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, (-)-Epigallocatechin-3-gallate (EGCG), a bioactive component found in green tea, can inhibit autophagy via the AKT/AMPK/mTOR phosphorylation pathway, thus preventing further reperfusion injury in the mouse brain. [59]…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving adult rats, after inducing middle cerebral artery occlusion injury, it was shown that EGCG exerted a neuroprotective effect by regulating caspase-3 and poly(adenosine diphosphate-ribose) polymerases (PARP) proteins during cerebral ischemia [94]. Another animal study confirmed that EGCG inhibited autophagy by modulating the protein kinase B (AKT)/5'adenosine monophosphate-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) phosphorylation pathway in both in vivo and in vitro models of stroke [95].…”
Section: Epigallocatechin Gallatementioning
confidence: 99%